Analysis of Bit Rate and Distance Variation on Multiplexing System of Indoor Li-Fi Technology Using Movable LED Panel - Fauza Khair; I Wayan Mustika; Nur Azizah; Anggun Fitrian Isnawati (Ikatan Ahli Informatika Indonesia (IAII), 2023)
The major problem of using light fidelity (Li-Fi) technology is still limited to the line of sight (LOS) conditions, which poses a challenge to perform bandwidth efficiency to support increased bit rates, especially for indoor use. In addition, the distance between the lamp driver (transmitter) and the receiver becomes a critical discussion to determine the characteristics of propagation losses. Therefore, this study focuses on analyzing the performance of an indoor Li-Fi multiplexing system using a movable LED panel (LP) based on parameters of bit rate and distance variation on multiple-input multiple-output (MIMO) 2x2 and 4x4. The parameter analysis of signal quality included optical and electrical signal spectrum characteristics, signal-to-noise ratio (SNR), bit error rate (BER), and Q-factor parameters. Based on the results, the increase in bit rate and distance significantly increases the BER value and decreases the Q-factor value. Both the 2x2 and 4x4 mux systems can meet standards up to a bit rate of 30 Mbps at a LOS distance of 3 meters, while at a bit rate of 40 Mbps, there are no channels that meet the ITU-T standard. In addition, the quality of the signal received at a distance of 4 meters, the 2x2 mux system can only reach the standard at a bit rate of 20 Mbps for all channels. However, channel 3 and channel 4 on the 4x4 mux system model still have the BER and Q-factor values that meet the standard in the bit rate of 30 Mbps. However, the decrease in the SNR value affected by the bit rate increase and distance is insignificant. Therefore, it becomes an opportunity for further observation of the proposed multiplexing system, detection scheme, or responsivity, and signal processing on the receiver side to be reliable on the higher bit rate.